Heterodissemination: precision insecticide delivery to mosquito larval habitats by cohabiting vertebrates - Isik Unlu (Nature Portfolio, 2021)
Abstract Conventional larvicide delivery strategies originally developed for permanent and floodwater mosquitoes have proved suboptimal in the small, scattered, and cryptic larval habitats preferred by container-inhabiting Aedes mosquitoes. New methods such as autodissemination, wherein adult mosquitoes spread insecticides to their own larval habitats, have been under study. Another novel delivery method termed heterodissemination, i.e. larvicide delivery by other species sharing the same habitats, has also been proposed. We conducted a proof-of-concept study with four independent experiments using American bullfrogs (Lithobates catesbeianus) and green frogs Lithobates clamitans as carriers of pyriproxyfen, an insect growth regulator, under semi-field conditions in three different locations, two in New Jersey, and one in Utah. Frogs with attached slow-release pyriproxyfen tablets were introduced into outdoor enclosures with water containers. Water samples from the containers were periodically tested using larval Aedes albopictus and Culex pipiens mosquitoes to assess mortality and percent eclosure inhibition. Overall pupal mortality [95% credible intervals] estimated by Bayesian analysis for the treatment group was 73.4% [71.3–75.2] compared to 4.1% [2.9–5.5] for the control group. Mortality within treatment groups in four different experiments ranged from 41 to 100%, whereas control mortalities ranged from 0.5% to 11%. We conclude that heterodissemination is a promising and effective approach deserving of further study.